2023
DOI: 10.3390/s23229059
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sex, Body Mass Index, Age, Exercise Type and Exercise Duration on Interstitial Glucose Levels during Exercise

Ninoschka C. D’Souza,
Durmalouk Kesibi,
Christopher Yeung
et al.

Abstract: The impact of age, sex and body mass index on interstitial glucose levels as measured via continuous glucose monitoring (CGM) during exercise in the healthy population is largely unexplored. We conducted a multivariable generalized estimating equation (GEE) analysis on CGM data (Dexcom G6, 10 days) collected from 119 healthy exercising individuals using CGM with the following specified covariates: age; sex; BMI; exercise type and duration. Females had lower postexercise glycemia as compared with males (92 ± 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…While TBR events were reasonably frequent in both men and women, averaging five occurrences per day with about 3.4% TBR, the duration was typically brief, (i.e., ~8 min per exercise-related occurrence vs. 11 min in the overnight period), and the gender differences could be deemed small (i.e., only 0.8% more TBR, which is equivalent to an extra 11 min per day < 70 mg/dL). Overall, the active males and females spent most of the time in the range of 70-140 mg/dL, as previously reported by D'Souza et al [18]. Taken together, these findings are in line with the notion that healthy individuals with intact glucose counterregulatory hormones have very little sustained exposure to biochemical hypoglycemia (glucose < 70 mg/dL) [19].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While TBR events were reasonably frequent in both men and women, averaging five occurrences per day with about 3.4% TBR, the duration was typically brief, (i.e., ~8 min per exercise-related occurrence vs. 11 min in the overnight period), and the gender differences could be deemed small (i.e., only 0.8% more TBR, which is equivalent to an extra 11 min per day < 70 mg/dL). Overall, the active males and females spent most of the time in the range of 70-140 mg/dL, as previously reported by D'Souza et al [18]. Taken together, these findings are in line with the notion that healthy individuals with intact glucose counterregulatory hormones have very little sustained exposure to biochemical hypoglycemia (glucose < 70 mg/dL) [19].…”
Section: Discussionsupporting
confidence: 88%
“…This large cohort study of active males and females complements other cohort studies of CGM metrics in the general population [14][15][16][17][18] but is the first to focus on glycemia during sleep and endurance exercise. Unlike these other smaller studies, these data reveal small differences between genders in overall 24 h glycemia, with women having slightly lower 24 h mean glucose levels as well as lower glucose levels in response to meals and sleep than men.…”
Section: Discussionmentioning
confidence: 86%
“…However, in recent years, the use of CGM for sports performance in nondiabetic athletes has emerged (41). Although the use of CGM in nonclinical conditions has been criticized, primarily because of a lack of data demonstrating their utility in the "healthy" population (42), other studies have demonstrated that, during exercise, apparently healthy and physically active individuals without diabetes often exhibit interstitial glucose levels outside of the tight glycemic range (70 to 120 mg•dL −1 ) (43,44). In addition, they can experience reactive hypoglycemia during exercise resulting from poorly timed CHO intake before the activity (45).…”
Section: Discussionmentioning
confidence: 99%